FAKTOR-FAKTOR YANG MEMPENGARUHI KENAIKAN HARGA SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA (BEI) - Arisya Eri Pradita, 09.05.52.0105; Lisiantara, G. Anggana (Students Journal of Accounting and Banking, 2013)
The purpose of this study is to examine and analyze the effect of Capital Adequancy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Performing Loan (NPL), Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM) the stock price partially. Populations used are banking companies in the Stock Exchange in 2008-2011, the number of samples by using purposive sampling techniques are as many as 26 companies. Types of data used are secondary data, in the form of financial statements. The results are: Return on Assets (ROA), Return on Equity (ROE), and net profit margin (NPM) significantly influence stock prices, this result proved the significance value <0.05. Capital Adequacy Ratio (CAR), Total Loan to deposit ratio (LDR), Non Performing Loan does not significantly affect the stock price., These results demonstrated the significant value> 0.05.Keywords: CAR, LDR, NPL, ROA, ROE, NPM and Stock Price Â